(3QSGdI JhHjN Hf CHj MUjIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3HSe GdEdg GdeeVi dCeQg hEQGOJg EPG CMH HeTjFJg hcdeJg CWGd Gddg HbGA GdTjhN GdMaXI GdCWgGQ hGdLeGYI GdaGVdI GdCNjGQ s
(3BNQgG (B:s
(3hef HMhRJg adjSgehg SgekG ef GdfYeI jef Hg Ydi ef CfS NjQg Je GdJhHjN hGdMeO dehdGfG hMOg hGdTcQ dhdjg GdgGOi YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B78s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds